20 March 2015 solar eclipse influence on sporadic E layer. Issue 10 (15th November 2015) - Pezzopane, M.; Pietrella, M.; Pignalberi, A.; Tozzi, R.
Abstract This paper shows how the solar eclipse occurred on 20 March 2015 influenced the sporadic E (Es) layer as recorded by the Advanced Ionospheric Sounder by Istituto Nazionale di Geofisica e Vulcanologia (AIS-INGV) ionosondes installed at Rome (41.8°N, 12.5°E) and Gibilmanna (37.9°N, 14.0°E), Italy. In these locations, the solar eclipse was only partial, with the maximum area of the solar disk obscured by the Moon equal to ∼54% at Rome and ∼45% at Gibilmanna. Nevertheless, it is shown that the strong thermal gradients that usually accompany a solar eclipse, have significantly influenced the Es phenomenology. Specifically, the solar eclipse did not affect the Es layer in terms of its maximum intensity, which is comparable with that of the previous and next day, but rather in terms of its persistence. In fact, both at Rome and Gibilmanna, contrary to what typically happens in March, the Es layer around the solar eclipse time is always present. On the other hand, this persistence is also confirmed by the application of the height–time–intensity (HTI) technique. A detailed analysis of isoheight ionogram plots suggests that traveling ionospheric disturbances (TIDs) likely caused by gravity wave (GW) propagation have played a significant role in causing the persistence of the Es layer.